Settlement of Defaults in Camera Rental Agreements at Jogja Lens Camera Shop - Pradana, Hendrico; Heriyani, Endang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The parties to the camera rental agreement should carry out the contents of the agreed agreement. In practice, the tenant does not carry out the contents of the agreement that has been agreed upon. Tenants who do not carry out the contents of the agreement are called defaulters. This study aims to determine the form of default and efforts to resolve defaults in camera rental agreements at Lensa Jogja. The type of research used in this research is normative empirical. The conclusion in this research is that the form of default that occurs in the camera rental agreement at Lensa Jogja, namely: the renter is late in returning the camera, returning the camera is not in accordance with the initial condition, losing the rented camera. The settlement of default in the camera rental agreement is to give a fine for the delay in returning the camera and compensation in the form of money or the same item for damage and loss of the rented camera.